Knowledge, attitudes and practices regarding HIV/AIDS of hotel staff from a selected hotel group in Cape Town - Mohammed, Amina (Cape Peninsula University of Technology, 2006)
The HIV/AIDS pandemic poses one of the greatest challenges to business development in South Africa. The hotel industry is growing rapidly and will be . significantly affected by the HIV/AIDS pandemic. The purpose of this study was to determine the Knowledge, Attitudes and Practices (KAP) regarding HIV/AIDS of staff from nine Protea group hotels in Cape Town. A sample of 200 hotel staff was randomly selected to participate. A structured self-administered anonymous questionnaire was the instrument used to collect the data. The response rate was 81%. There were more females than males, and the majority of the respondents were between the ages of 21-30 years. More than half of the respondents were single, hotel managers and with matriculation as the highest qualification. The respondents demonstrated a reasonably good knowledge on the transmission of HIV/AIDS. Almost half of the respondents believed that HIV/AIDS would not affect the hotel industry. The survey revealed conflicting results on whether HIV-infected staff should be involved in food preparation, and whether staff should serve food to HIV positive hotel guests. There were also concerns of the risk of infection when handling dirty linen used by HIV-infected hotel guests. More males than females were currently sexually active and reported having more than one partner in the past three years. The majority of the respondents believed that condoms were effective, but only one third reported the use of a condom every time they had a sexual encounter. There was a significant relationship between knowledge and attitudes (p-value<0.05, but none between knowledge and practice and attitude and practice. It is recommended that the hotel industry develop effective workplace policies and supportive environments, and that on-going HIV/AIDS education and prevention programmes be implemented to change high risk sexual behaviour and practices.
Thesis (MTech (Tourism and Hospitality Management))--Cape Peninsula University of Technology, 2006.
Keywords: HIV infections -- South Africa -- Prevention; AIDS (Disease) -- South Africa -- Prevention; HIV infections -- South Africa -- Social aspects